Answer:
0.73
Explanation:
Data obtained from the question include the following:
Length (L) of square = x
Base (b) of triangle = (3x – 2)
Height (h) of triangle = (2x + 4)
Area of square = L²
Area of square = x²
Area of triangle = ½bh
Area of triangle = ½(3x – 2) (2x + 4)
Expand
½ [3x(2x + 4) –2(2x + 4)]
½[6x² + 12x – 4x – 8]
½[6x² + 8x – 8]
3x² + 4x – 4
Area of triangle = 3x² + 4x – 4
Now, to find the value of x which makes the area of the two figures the same, we simply equate both areas as shown below:
Area of triangle = area of square
Area of triangle = 3x² + 4x – 4
Area of square = x²
Area of triangle = area of square
3x² + 4x – 4 = x²
Rearrange
3x² – x² + 4x – 4 = 0
2x² + 4x – 4 = 0
Solving by formula method
a = 2, b = 4, c = –4
x = – b ± √(b² – 4ac) / 2a
x = – 4 ± √(4² – 4×2×–4) / 2×2
x = – 4 ± √(16 + 32) / 4
x = – 4 ± √(48) / 4
x = (– 4 ± 6.93)4
x = (– 4 + 6.93)4 or (– 4 – 6.93)4
x = 0.73 or –2.73
Since the measurement can not be negative, the value of x is 0.73.